Sheikh Muhammad al-Ramoun al-Nadroumi- Forgotten Margins from the Memory of Poetry - (مجلة إحالات, 2026)
The cultural history of the city of Nedroma bears witness to this cultural, artistic, scientificand even literary dynamism in the city, given what we see in the books of biographies andtranslations of the notables of the central Maghreb, of stopping at many literary, scientific and political names that grew up in the city and were affiliated with it. And since this was the case, itwas necessary for masters of speech and masters of the horizons of poetic creativity to graduatefrom this cultural momentum. In the field of Malhoun poetry, those working on this art studied the texts of one of the city’smost famous poets, Sheikh Qaddour bin Ashour Al-Zarhouni, who is considered the most famousand prolific poet in the city. He has been the subject of many studies, especially after the publication of his collection of poems, which was compiled by Muhammad bin Amr Al-Zarhouni. However, many names remained forgotten and on the margins of work, and their texts were notcollected or verified, including Sheikh Muhammad al-Ruma’un, who is considered the dean of Malhun poetry in the city. We are trying to remove the veil of marginalization from him as a nameand as a text through this research paper that seeks to introduce him and his texts.